‎ SWOLLEN HEAD SYNDROME IN BROILER CHICKENS - A. Abdul-Aziz‎, T.; J. Khammas‎, E.; M. Jawad‎, G. (The Iraqi Journal of Veterinary Medicine, 1986)
The clinical, microbiologic and pathologic findings of swollen head syndrome in broiler chickens in Iraq are reported in this study. A consistent clinical feature of this syndrome was swelling of the face. The facial subcutaneous tissue, conjunctivae and nictitating membranes were edematous. Microscopically, there was acute or chronic dermatitis and cellulitis characterized by necrosis of the dermis and subcutaneous tissues, with infiltration by heterophils in acute cases and by macrophages and giant célls in chronic cases. Esherichia coli was constatnly isolated from the facial subcutaneous tissue.